Chronic stress dampens excitatory synaptic gain in the paraventricular nucleus of the hypothalamus. (22nd July 2018) - Salter, Eric W.; Sunstrum, Julia K.; Matovic, Sara; Inoue, Wataru
Abstract : Key points: Glutamatergic synaptic inputs to corticotrophin‐releasing hormone (CRH) secreting neurons in the paraventricular nucleus of the hypothalamus (PVN) are required for stress‐induced activation of the hypothalamic‐pituitary‐adrenal (HPA) axis. These synapses also undergo stress‐induced plasticity, thereby influencing HPA axis stress adaptation. By using patch clamp electrophysiology, we show that, in adult non‐stressed mice, action potentials at these glutamatergic afferents elicit multiquantal transmission to the postsynaptic PVN‐CRH neurons (i.e. synaptic multiplicity). Mechanistically, synaptic multiplicity results from multivesicular release at common synaptic sites, which is facilitated upon elevation of release probability, effectively increasing the upper limit of the dynamic range of synaptic transmission. Following chronic variable stress, functional PVN glutamate synapse number increases, although its synaptic multiplicity paradoxically decreases. These two contrasting synaptic changes can, respectively, increase the baseline excitatory drive while also limiting the capacity for potentiation, and may preferentially increase the baseline excitatory drive onto PVN‐CRH neurons. Abstract: The activation of the hypothalamic‐pituitary‐adrenal (HPA) axis relies on excitation of neuroendocrine neurons in the paraventricular nucleus of the hypothalamus (PVN) that secrete corticotrophin‐releasing hormone (CRH). Afferent glutamate synapses onto these PVN‐CRH neurons convey critical excitatory inputs during stress, and also undergo stress‐induced plasticity, highlighting their roles in both stress activation and adaptation of the HPA axis. In the present study, using whole‐cell patch clamp recordings from PVN‐CRH neurons in brain slices from adult mice, we found that the amplitude of action potential‐dependent spontaneous EPSCs (sEPSCs) was larger than that of action potential independent miniature EPSCs (mEPSCs), suggesting that action potentials at individual axons recruited multiquantal transmission onto the same postsynaptic neurons (i.e. synaptic multiplicity). The large, putative multiquantal sEPSCs had fast rise times similar to mEPSCs, and were abolished by replacing extracellular Ca 2+ with Sr 2+, indicating Ca 2+ ‐dependent synchronous release of multiple vesicles. Application of a low affinity, fast dissociating competitive AMPA receptor antagonist γ‐d ‐glutamylglycine revealed that synaptic multiplicity resulted from multivesicular release targeting a common population of postsynaptic receptors. High‐frequency afferent stimulation facilitated synaptic multiplicity, effectively increasing the upper limit of the dynamic range of synaptic transmission. Finally, we found that chronic variable stress (CVS), a stress model known to cause basal HPA axis hyperactivity, increased sEPSCs frequency but paradoxically decreased synaptic multiplicity. These results suggest that the CVS‐induced synaptic changes may elevate the baseline excitatory drive at the same time as limiting the capacity for potentiation, and may contribute to the basal HPA axis hyperactivity. Key points: Glutamatergic synaptic inputs to corticotrophin‐releasing hormone (CRH) secreting neurons in the paraventricular nucleus of the hypothalamus (PVN) are required for stress‐induced activation of the hypothalamic‐pituitary‐adrenal (HPA) axis. These synapses also undergo stress‐induced plasticity, thereby influencing HPA axis stress adaptation. By using patch clamp electrophysiology, we show that, in adult non‐stressed mice, action potentials at these glutamatergic afferents elicit multiquantal transmission to the postsynaptic PVN‐CRH neurons (i.e. synaptic multiplicity). Mechanistically, synaptic multiplicity results from multivesicular release at common synaptic sites, which is facilitated upon elevation of release probability, effectively increasing the upper limit of the dynamic range of synaptic transmission. Following chronic variable stress, functional PVN glutamate synapse number increases, although its synaptic multiplicity paradoxically decreases. These two contrasting synaptic changes can, respectively, increase the baseline excitatory drive while also limiting the capacity for potentiation, and may preferentially increase the baseline excitatory drive onto PVN‐CRH neurons.